Investigation of Attitudes Towards Business Outcomes and Patient Safety in Comparison with Video and Physical Consultation - John Sen, Elizabeth (Global journal of Business and Integral Security, 2024)
Background During and after the COVID-19 pandemics, healthcare delivery has undergone a significant change, easily noticeable by the integration of technology into traditional practices. The situation is that starting virtual consultations, facilitated by advancements in telemedicine and communication technologies, has reshaped the dynamics of patient- physician interactions. As healthcare professionals increasingly adapt both video and physical consultation modalities, understanding their attitudes towards business outcomes and patient safety becomes more important than anything else. The fact that video and physical consultations are held side by side or close together raises interesting questions about healthcare professionals’ perceptions and preferences. The healthcare industry, characterized by its complexity and dynamic nature, demands a nuanced examination of the economic and safety implications associated with these consultation methods. The decisions made in this regard have far-reaching consequences for practitioners, patients, and the healthcare system at large.